Endovascular treatment of dural arteriovenous fistulas with sinus drainage: Do we really need to protect the sinus?. Issue 3 (June 2019) - Kortman, Hans; Boukrab, Issam; Sluzewski, Menno; van Rooij, Willem Jan; Peluso, Jo PP; Majoie, Charles
Background and purpose: Dural arteriovenous fistulas (DAVFs) with direct antegrade sinus drainage have a benign natural history but bruit can be disabling. Disconnection of the draining sinus is considered curative. We present the treatment results of 14 patients with a dural arteriovenous fistula with antegrade sinus return with emphasis on functionality of the involved sinus and the need for sinus patency. Materials and methods: Between January 2009 and January 2018, 14 patients with a DAVF with direct antegrade sinus drainage were treated in our institution. There were two men and 12 women (1: 6) with a mean age of 61 years (median 61, range 43–78). Clinical presentation was unbearable pulsatile bruit in all cases. Thirteen were draining in the sigmoid or transverse sinus and one drained into the inferior petrosal sinus. Results: Twelve of 14 (86%) patients had a draining sinus non-functional for the brain. In ten of these 12 patients the sinus was occluded with liquid embolic or coils. In the two patients with a functional sinus, the fistula was successfully occluded without occluding the sinus. One patient with inferior petrosal sinus drainage required transvenous embolization. There were no permanent adverse events of treatment. Conclusions: Patients with DAVFs with direct antegrade sinus drainage were cured using a strategy of endovascular transarterial and transvenous embolization. Most patients had a non-functional sinus that could be occluded for cure.